Novel APC gene mutations associated with protein alteration in diffuse type gastric cancer - Souvik Ghatak; Payel Chakraborty; Sandeep Roy Sarkar; Biswajit Chowdhury; Arup Bhaumik; Nachimuthu Senthil Kumar (BMC, 2017)
Abstract Background The role of adenomatous polyposis coli (APC) gene in mitosis might be critical for regulation of genomic stability and chromosome segregation. APC gene mutations have been associated to have a role in colon cancer and since gastric and colon tumors share some common genetic lesions, it is relevant to investigate the role of APC tumor suppressor gene in gastric cancer. Methods We investigated for somatic mutations in the Exons 14 and 15 of APC gene from 40 diffuse type gastric cancersamples. Rabbit polyclonal anti-APC antibody was used, which detects the wild-type APC protein and was recommended for detection of the respective protein in human tissues. Cell cycle analysis was done from tumor and adjacent normal tissue. Results APC immunoreactivity showed positive expression of the protein in stages I, II, III and negative expression in Stages III and IV. Two novel deleterious variations (g.127576C > A, g.127583C > T) in exon 14 sequence were found to generate stop codon (Y622* and Q625*)in the tumor samples. Due to the generation of stop codon, the APC protein might be truncated and all the regulatory features could be lost which has led to the down-regulation of protein expression. Our results indicate that aneuploidy might occurdue to the codon 622 and 625 APC-driven gastric tumorigenesis, in agreement with our cell cycle analysis. The APC gene function in mitosis and chromosomal stability might be lost and G1 might be arrested with high quantity of DNA in the S phase. Six missense somatic mutations in tumor samples were detected in exon 15 A-B, twoof which showed pathological and disease causing effects based on SIFT, Polyphen2 and SNPs & GO score and were not previously reported in the literature or the public mutation databases. Conclusion The two novel pathological somatic mutations (g.127576C > A, g.127583C > T) in exon 14 might be altering the protein expression leading to development of gastric cancer in the study population. Our study showed that mutations in the APC gene alter the protein expression and cell cycle regulation in diffuse type gastric adenocarcinoma.